2004
DOI: 10.1002/prot.20243
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic studies of V44 mutants of Clostridium pasteurianum rubredoxin: Effects of side‐chain size on reduction potential

Abstract: Understanding the structural origins of differences in reduction potentials is crucial to understanding how various electron transfer proteins modulate their reduction potentials and how they evolve for diverse functional roles. Here, the high-resolution structures of several Clostridium pasteurianum rubredoxin (Cp Rd) variants with changes in the vicinity of the redox site are reported in order to increase this understanding. Our crystal structures of [V44L] (at 1.8 A resolution), [V44A] (1.6 A), [V44G] (2.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Detailed comparison of available x-ray crystal structures of CpRd variants has revealed that slight changes in the structure surrounding the iron-sulfur cluster are responsible for the range of observed reduction potentials (15,16,28). In our study, 15 N hyperfine shifts were used to detect subtle changes in H N ⅐⅐⅐⅐⅐S ␥ bond lengths in CpRd variants.…”
Section: Discussionmentioning
confidence: 89%
“…Detailed comparison of available x-ray crystal structures of CpRd variants has revealed that slight changes in the structure surrounding the iron-sulfur cluster are responsible for the range of observed reduction potentials (15,16,28). In our study, 15 N hyperfine shifts were used to detect subtle changes in H N ⅐⅐⅐⅐⅐S ␥ bond lengths in CpRd variants.…”
Section: Discussionmentioning
confidence: 89%
“…16,[29][30][31][32][33] We distinguish three types of H-bonds ( Figure 1a) (HB1, HB2, HB3, depicted in Scheme 1). Each of the ISC sulfur atoms, S1 and S3, is engaged in two H-bonds, which we call type HB1 and HB2.…”
Section: Isc H-bonds In Rdmentioning
confidence: 99%
“…Investigations of thermally induced unfolding of CpRd showed that loss of the metal ion immediately precedes formation of the (apparently) unstructured apoRd [19], but that Fe(SCys) 4 site stability does not control the thermostability of the native folded structure [20]. Engineered V ↔ A exchanges of residue 44, which forms an N-H…S hydrogen bond to one of the ironcoordinating Cys residues, significantly raised and lowered the respective stabilities of the Fe(SCys) 4 sites in CpRd and PfRd [21][22][23][24] but had only minor effects on the thermal stabilities of the folded holoRds. Thiophilic metal ions (Cd II , Zn II ) can directly and isomorphically displace iron from the native Fe II (SCys) 4 site of CpRd under nondenaturing conditions and without unzipping of the β-sheet [25].…”
Section: Introductionmentioning
confidence: 99%